Intersectionality: A Systematic Review of the Application of the Concept in Studies on Ghana - Odum-Sackey, Bismark (Advances in Social Sciences Research Journal, 2022)
The concept of intersectionality, since its birth in the nineteenth century, has since evolved and broadened across disciplines transcending feminism and race. The intersectionality approach has gained a lot of traction recently, resulting in the application of the concept in various forms and meanings, spanning various geographical locations. This study sought to identify published journal articles employing the intersectionality approach within the Ghanaian context between January 2020 and September 2022, and examine how intersectionality has been conceptualized in research.The study employed the systematic review approach, using the Google Scholar database and EBSCOhost. A literature search was conducted using the "intersectionality AND Ghana" search string. From the review, it was revealed that intersectionality has been conceptualized in the Ghanaian context across many identities including but not limited to gender, race, marital status, and social class. The thematic areas in the papers included health, agriculture, leadership and politics, sexual exploitation, and violence. Despite the increasing popularity of the intersectionality approach on the global front, the Ghanaian context still needs in-depth empirical studies using rigorous methodological approaches and better operationalized theoretical underpinnings to better understand the conceptual issues related to intersectionality in Ghana.